2019
DOI: 10.3390/membranes9120160
|View full text |Cite
|
Sign up to set email alerts
|

Tangential Flow Filtration for the Concentration of Oncolytic Measles Virus: The Influence of Filter Properties and the Cell Culture Medium

Abstract: The therapeutic use of oncolytic measles virus (MV) for cancer treatment requires >108 infectious MV particles per dose in a highly pure form. The concentration/purification of viruses is typically achieved by tangential flow filtration (TFF) but the efficiency of this process for the preparation of MV has not been tested in detail. We therefore investigated the influence of membrane material, feed composition, and pore size or molecular weight cut-off (MWCO) on the recovery of MV by TFF in concentration mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…These methods include density gradient ultracentrifugation (gUC), filtration, and various chromatographies (Staubach et al, 2021), such as size exclusion chromatography (SEC), ion exchange chromatography (IEX), and affinity chromatography (AC) (Paganini et al, 2019). A reliable method extensively used for liposomes (Worsham et al, 2019) as well as for virus isolation (Loewe et al, 2019) and now adopted in the EV field is tangential flow filtration (TFF) (Heinemann et al, 2014;Busatto et al, 2018;Haraszti et al, 2018). In TFF, the particle solution, or the cell culture, flows tangentially over a membrane with a given size cut-off.…”
Section: Isolation By Differential Tangential Flow Filtrationmentioning
confidence: 99%
“…These methods include density gradient ultracentrifugation (gUC), filtration, and various chromatographies (Staubach et al, 2021), such as size exclusion chromatography (SEC), ion exchange chromatography (IEX), and affinity chromatography (AC) (Paganini et al, 2019). A reliable method extensively used for liposomes (Worsham et al, 2019) as well as for virus isolation (Loewe et al, 2019) and now adopted in the EV field is tangential flow filtration (TFF) (Heinemann et al, 2014;Busatto et al, 2018;Haraszti et al, 2018). In TFF, the particle solution, or the cell culture, flows tangentially over a membrane with a given size cut-off.…”
Section: Isolation By Differential Tangential Flow Filtrationmentioning
confidence: 99%
“…Resistance-in-series analysis considers the total filtration resistance as the sum of all partial resistances of different causes, here defined as membrane resistance (R M ), gel layer resistance caused by concentration polarization of protein aggregates (R g ), and adsorption resistance from the adsorption of cell lysate proteins to the membrane (R a ). This model has been successfully applied to the filtration of biological solutions containing cells (Fan et al, 2015), viruses (Loewe et al, 2019), and enzymes (Fan et al, 2020). Different approaches to applying resistance-in-series have recently been reviewed extensively (Di Bella and Di Trapani, 2019).…”
Section: Resistance-in-series Modelmentioning
confidence: 99%
“…Very high values of water recovery are likely to lead to membrane fouling and related virus losses. By the same token, if low r is a result of increasing crossflow rate (e.g., to combat fouling) while maintaining the same permeate flow rate, one can reach shear stresses in the membrane channel that may damage fragile biologics such as enveloped viruses 23‐25 . For example, Grein et al have shown that Measles virus titers are sensitive to shear, with shear stress of 0.25 Pa and higher reducing the virus titer by more than four orders of magnitude 26 …”
Section: Practical Value and Potential Extensions Of The Modelmentioning
confidence: 99%